PTU-112 Associations Between Healthcare Resource Utilisation And Health-related Quality Of Life In Cirrhosis. (9th June 2014) - Orr, J; Homer, T; Ternent, L; Vale, L; Hudson, M; Jones, D
Abstract : Introduction: Cirrhosis is associated with impaired Health-Related Quality of Life (HRQoL) and considerable resource use. The association between healthcare utilisation and HRQoL in cirrhosis has not been previously studied. Methods: Four HRQoL tools (SF-36v2, CLDQ, PBC-40 and PROMIS-HAQ) and a healthcare utilisation tool were completed by patients with cirrhosis. Associations between resource utilisation and HRQoL were explored; means were compared using unpaired t tests. Results: 108 patients have been recruited to the study to date with completed tools received from 73. Regular care was required by 29 (40%) with 15 (21%) requiring help with personal care, 12 (16%) with medical care, 18 (25%) with meal preparation and 21 (29%) with housework. All types of care were associated with significantly impaired HRQoL across all domains of all measures tested (p < 0.05). The total number of healthcare consultations (hospital consultations + GP consultations + nurse consultations) was also related to HRQoL with patients who had five or more consultations in a 2 month period showing significant impairment compared to patients with fewer than five consultations. Specifically there was evidence of poorer physical HRQoL with mean SF-36 Physical Component Summary (PCS): 32.5 ± 9.0 vs 40.6 ± 10.6, p = 0.001 and functional restriction evidenced by PROMIS-HAQ: 42.2 ± 26.9 vs 21.1 ± 25.2, p = 0.001. In addition, patients with more consultations had poorer social HRQoL with SF-36 Social Functioning (SF): 31.3 ± 12.3 vs 40.2 ± 12.8, p = 0.005 and PBC-40 social: 36.3 ± 9.9 vs 30.0 ± 9.7 p = 0.01. Conclusion: The need for any type of regular care and more frequent consultations with healthcare professionals are associated with poorer HRQoL in cirrhosis. Disclosure of Interest: None Declared.